Effects of Sevoflurane and Propofol on Posttraumatic Stress Disorder After Emergency Trauma: A Double-Blind Randomized Controlled Trial - Zhong, Junfeng; Li, Yan; Fang, Lichao; Han, Dan; Gong, Chuhao; Hu, Shuangyan; Wang, Rongguo; Wang, Liwei; Yao, Rui; Li, Beiping; Zhu, Yangzi; Yu, Youjia (Frontiers in Psychiatry, 2022)
Objective: Posttraumatic stress disorder (PTSD) is a frequent and disabling consequence of traumatic events. A previous study found that early use of propofol was a potential risk factor for PTSD. This study aimed to investigate the effect of propofol and sevoflurane on PTSD after emergency surgery in trauma patients. Methods: A total of 300 trauma patients undergoing emergency surgery were randomly divided into two groups and anesthetized with propofol and/or sevoflurane. Perioperative clinical data were collected. The incidence of PTSD was evaluated with the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) in the two groups one month after the operation. The relevance of the injury time and CAPS-5 scores was assessed by Spearman correlation analysis. Logistic regression analysis was used to analyze the risk factors for PTSD. Results: The incidence of PTSD in the propofol group was higher than that in the sevoflurane group 1 month postoperatively (23.2% vs. 12.2%, P=0.014). The injury time was negatively correlated with the CAPS-5 score in the propofol group (r=-0.226, P<0.001). In the logistic regression analysis, the utilization of propofol was an independent risk factor for PTSD (P=0.014). Conclusion: Early use of propofol general anesthesia in emergency surgery for trauma patients may increase the risk of PTSD.